Evaluasi terhadap Pelaksanaan Komunikasi Pemasaran Sosial Non-Goverment Organization (NGO) untuk Isu-Isu Anti Kekerasan terhadap Perempuan (Studi Kasus Kampanye Anti Kekerasan Terhadap Perempuan Cut Nyak Dien Yogyakarta dan Solidaritas Perempuan untuk Ha - Nur R, Tri Hastuti (FISIP Universitas Atma Jaya Yogyakarta, 2006)
Abstract: This paper explains how social marketing communication used by Cut Nyak Dien, Yogyakarta and Spekham, Surakarta–those are non goverment organization (NGO)– to sosialize issues about anti-violences to women. The result of research show evaluation fase in the social marekting fases were not done. They were not evaluate the messages were received or not;and they were not identify the level of target audiens’ behaviour changes. The media that they used were variatives. Having social marketing communication, they always do with advocacy activities.